Stalk-eyed wasps—review of a largely unnoticed group of morphologically bizarre chalcidoid wasps (Hymenoptera: Eurytomidae: Axima) - Arias-Penna, Diana Carolina; Pape, Thomas; Krogmann, Lars (Zootaxa, 2014)
Axima Walker is a small genus of Eurytomidae (Hymenoptera: Chalcidoidea) exclusive to the Western Hemisphere. Some species are distinctive in having stalked eyes and Axima sidi, sp. n. is described as the third stalk-eyed species based on a single female from Colombia. A key to facilitate species identification of stalk-eyed Axima is included. The only species of Axima for which host biology is known is a primary parasitoid of dwarf carpenter bees of the genus Ceratina Latreille (Apidae: Xylocopinae). A hypothesis about the possible function of stalked eyes in Axima as devices to assist the escape of adult wasps from hosts enclosed in the soft pith of plant stems is proposed.